PEMANFAATAN FASILITAS KAWASAN DESA WISATA DALAM MENINGKATKAN EKONOMI MASYARAKAT DI DESA PONTOLO ATAS KECAMATAN KWANDANG KABUPATEN GORONTALO UTARA - Ari Putra Rachman; Dewi Sartika T. Zees; Aditya Rauf (Jurnal Pengabdian kepada Masyarakat (J-PMas), 2022)
The tourism sector is one of the mainstay sectors in boosting economic growth in today's modern era. The target of planning the development of a Tourism Village based on environment and community participation is all stakeholders and parties related and involved with development in Pontolo Atas Village, District. Kwandang, Kab. North Gorontalo. The activity aims to increase students' insight and skills in the professional field so that they are able to understand problematic issues that exist in society and can provide solutions to solve problems that exist in society.